Specific Features of the Qualification of War Crimes Against Property Involving Elements of Theft (Law and Safety, 2025)
The article is devoted to the development of theoretical foundations and practical recommendations for the correct classification of war crimes directed against property and involving elements of theft. Additional arguments are presented in favour of interpreting theft as the unlawful removal of property from the owner’s possession against their will, as well as the conversion of such property for the benefit of other persons. Approaches to the classification of war crimes against property are identified, provided that it is recognised as an additional optional object of encroachment, which depends on both the perpetrator of the crime and the characteristics of the object, the victim, the method and context of the socially dangerous act. Three typical situations of criminal law classification have been established and characterised, and a number of legal options have been identified within which the grounds for classification are determined, either as a war crime under Article 438 of the Criminal Code of Ukraine, or as a military offence with signs of a war crime, including looting (Articles 432, 433 of the Criminal Code of Ukraine), or as an ordinary criminal offence. The characteristics of the international legal blanket nature of the disposition of Part 1 of Article 438 of the Criminal Code of Ukraine in terms of causing damage to property in conditions of armed conflict as a result of acts with signs of theft are provided.It has been proven that acts involving theft, robbery, extortion, appropriation of civilian property, and unlawful seizure of vehicles committed by combatants on the side of the russian federation should be classified under Part 1 of Article 438 of the Criminal Code of Ukraine as other violations of the laws and customs of war provided for by international treaties, the binding nature of which has been approved by the Verkhovna Rada of Ukraine. 438 of the Criminal Code of Ukraine as other violations of the laws and customs of war provided for by international treaties, the binding nature of which has been approved by the Verkhovna Rada of Ukraine. This classification is based on the violation of the prohibition on the appropriation of such property, established by Part 1 of Article 53 of the Hague Convention of 1907, Article 147 of the Geneva Convention relative to the Protection of Civilian Persons in Time of War of 1949, and Rule 51 of Customary International Humanitarian Law. It is emphasised that this rule of criminal law classification is also applicable to a corresponding group of acts committed by civilians who are agents of the occupation. Such persons may include both citizens of the aggressor state and citizens of Ukraine who, as a result of predicate collaboration activities (Parts 5–7 of Article 111-1 of the Criminal Code of Ukraine), have acquired the status of subjects of occupation.
Keywords: war; armed conflict; classification; war crime; military criminal offence; contextual element; theft; looting.